Log in to add a comment

Log in to add a comment

X=7/2Y

3X-Y=18

3*7/2Y-Y=18

21/2Y-Y=18

21-2Y²=36Y

2Y²+36Y-21=0

X=(-36+-√36²-4(2)(21))/2*2

⇒(-36+-√1296+168)/4⇒(-36+-√1464)/4⇒

1) 3x - y = 18

2) 2xy = 7

in order to solve this pair of equations, we need to derive a relationship between x and y. So letus take the first equation

3x - y = 18

taking y to RHS and 18 to LHS(keeping sign convention in mind)

we get 3x - 18 = y

so now we substitute this value of y in our second equation which was

2xy = 7

which gives us 2x (3x - 18) =7

now upon opening the braces, we get

6 - 36x - 7 = 0

now we need to solve the quadratic equation in x to determine the possible values of x

x = (-36+)/2*6

this leaves us at x = (-36 + 38.226)/12 = 0.1885

therby y = (3x - 18) = -17.435

or x = (-36 - 38.226)/12 = 74.226

therby y = (3x - 18) = 204.628

P.S( what i felt after reading the question is that the aqsker mightve missed a '+' sign in the second eqn, if that is the case, then

3x - y = 18

2x + y = 7

adding both eqns, 5x = 25; x = 5

hence y = -3; which seems a lot more simpler)